Increase in the glucosylated form of erythrocyte Cu-Zn-superoxide dismutase in diabetes and close association of the nonenzymatic glucosylation with the enzyme activity - Arai, Katsura; Iizuka, Susumu; Tada, Yoshihiko; Oikawa, Kiyoshi; Taniguchi, Naoyuki (Biochimica et biophysica acta, 1987)
Human erythrocytes contain glucosylated and nonglucosylated CuZnsuperoxide dismutases which can be separated by boronate affinity chromatography. The percentage of the glucosylated form is significantly increased in the erythrocytes of patients with diabetes as compared to normal erythrocytes. The nonglucosylated form of CuZnsuperoxide dismutase, which was washed through the boronate column, was glucosylated in vitro upon exposure to radioactive or non-radioactive D-glucose. Incorporated of D-glucose into the protein was observed, and with the increase in glucosylation, the enzymatic activity decreased, indicating that the glucosylation of the enzyme led to a low active form. This is the first demonstration that superoxide dismutase is glucosylated in erythrocytes and that the glucosylation leads to the inactivation of the enzyme.